USULAN PENERAPAN METODE SIX SIGMA DENGAN KONSEP DMAIC UNTUK PENINGKATAN KUALITAS OUTSOLESEPATU SPORT CAPSULE MEREK GEOFF PADA PERUSAHAAN OUTSOLE DI TANGERANG - Prita Agustin; Himawan Hendro Santopo; Diana Ross Arief (Politeknik ATK Yogyakarta, 2017)
As a shoe bottom component, outsole has an important role to give comfort and safety for users, therefore its quality must fulfill the standard. Defect of a product is one of quality indicator which can be directly noticed by consumers. The purpose of this study is to provide information about the application of Six Sigma method with DMAIC concept to improve the outsole quality of sports capsule shoes “Geoff”. Data of the outsole production of sport capsule shoes “Geoff” are required. The results show that the dominant defect is colour migration. The calculation shows that DPU is valued 0,2123, DPO 0,0009097, DPMO 14,2146, and sigma 3; and the result of statistic test for Chi – Square is 4,628. The analyzed result shows that the defect is caused by several factors, they are material, human, machine and method. Repairing action of the defect is done by using Poka – Yoke. The Six Sigma can be applied to Outsole Company in order to suppress the defect until it reaches the least value (Zero Defect) i.e. 3,4 ppm.